Tracer l’animal dans les nouvelles de Rick Bass - Claire Cazajous-Augé (Transatlantica, 2017)
In Rick Bass’s short stories, the descriptions of animals often seem fragmentary. Rather than aiming at an exhaustive representation of animals, the author resorts to fragmentary descriptions that show the elusive dimension of the nonhuman world. These traces thus show that something resists the human attempt to intellectually and physically capture animals. When an animal appears in the wilderness or in the text, it disturbs the course of the narrative. However, far from threatening the course of the story, the appearances of animals allow the author to question his ways of writing about the nonhuman world. Through descriptions of animals that try to hide from man’s gaze, Rick Bass creates a scriptural and physical approach that not only allows the author to redefine the descriptive mode, but also renews the relations between man and the nonhuman world. Surprisingly enough, the elusive dimension of the animals ultimately contributes to reinvent the relationships between humans.